ANSWER
A. x-8
EXPLANATION
The given functions are:
![f(x) = {x}^{2} - 11x + 24](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2024)
We factor this to get,
![f(x) = (x - 8)(x - 3)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20-%208%29%28x%20-%203%29)
and
![g(x) = x - 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20x%20-%203)
![( \frac{f}{g} )(x) = \frac{f(x)}{g(x)}](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bf%7D%7Bg%7D%20%29%28x%29%20%3D%20%20%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%20)
![( \frac{f}{g} )(x) = \frac{ {x}^{2} - 11x + 24}{x - 3} \: for\: x \ne3](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bf%7D%7Bg%7D%20%29%28x%29%20%3D%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2024%7D%7Bx%20-%203%7D%20%20%5C%3A%20%20for%5C%3A%20x%20%5Cne3)
![( \frac{f}{g} )(x) = \frac{(x - 8)(x - 3)}{x - 3}](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bf%7D%7Bg%7D%20%29%28x%29%20%3D%20%20%5Cfrac%7B%28x%20-%208%29%28x%20-%203%29%7D%7Bx%20-%203%7D%20)
Cancel the common factors to get,
![( \frac{f}{g} )(x) = x - 8](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bf%7D%7Bg%7D%20%29%28x%29%20%3D%20x%20-%208)
4396.6 bc the different between the years was 22 and 2060 thousand people and that divided is 93.6 and 3835 +93.6(6) is 4396.6 bc the 6 you multiply by is from the difference of 1998 and 1992
Answer:
x = 4
Step-by-step explanation:
Simplifying
3x + 15 = 6x + 3
Reorder the terms:
15 + 3x = 6x + 3
Reorder the terms:
15 + 3x = 3 + 6x
Solving
15 + 3x = 3 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
15 + 3x + -6x = 3 + 6x + -6x
Combine like terms: 3x + -6x = -3x
15 + -3x = 3 + 6x + -6x
Combine like terms: 6x + -6x = 0
15 + -3x = 3 + 0
15 + -3x = 3
Add '-15' to each side of the equation.
15 + -15 + -3x = 3 + -15
Combine like terms: 15 + -15 = 0
0 + -3x = 3 + -15
-3x = 3 + -15
Combine like terms: 3 + -15 = -12
-3x = -12
Divide each side by '-3'.
x = 4
Simplifying
x = 4
The ratio is - 6:12
(6 boys, 12 girls)
Answer:0.625
Step-by-step explanation:
Given
There are two coins one is fair and another is bent
Probability of getting a head on fair coin is 0.5
Probability of getting a head on bent coin is 0.75
If both coins are tossed once
probability of getting at least one of the coin will come up tails is
![P=1-P(both\ heads)](https://tex.z-dn.net/?f=P%3D1-P%28both%5C%20heads%29)
![P=1-0.5\times 0.75](https://tex.z-dn.net/?f=P%3D1-0.5%5Ctimes%200.75)
![P=1-0.375](https://tex.z-dn.net/?f=P%3D1-0.375)
![P=0.625](https://tex.z-dn.net/?f=P%3D0.625)